1989
DOI: 10.1042/bj2580607
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for altered expression of the GTP-dependent regulatory proteins, Gs and Gi, in adipocytes from aged rats

Abstract: The alpha-subunits of Gi and Gs were quantified in adipocyte membranes from young (2-month) and older (18-month) rats by pertussis-toxin and cholera-toxin labelling respectively. Aging was associated with a 3-fold increase in Gi alpha-subunit, but only a 2-fold increase in one of the two Gs alpha-subunit species labelled. The findings may explain the altered sensitivity of adipocytes from aged rats to lipolytic and anti-lipolytic stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 28 publications
(28 reference statements)
3
5
0
Order By: Relevance
“…Cholera-toxin-catalysed ADP-ribosylation has been used on several occasions to establish the relative amounts of a-Gs in plasma membranes [11,20,27]. In agreement with the reports quoted above, cholera toxin catalysed the ADP-ribosylation of two major peptides of 42 kDa and 46-48 kDa in plasma membranes isolated from rat adipocytes (Fig.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Cholera-toxin-catalysed ADP-ribosylation has been used on several occasions to establish the relative amounts of a-Gs in plasma membranes [11,20,27]. In agreement with the reports quoted above, cholera toxin catalysed the ADP-ribosylation of two major peptides of 42 kDa and 46-48 kDa in plasma membranes isolated from rat adipocytes (Fig.…”
Section: Resultssupporting
confidence: 80%
“…Diabetes has been reported to alter the expression and phosphorylation state of a-G1 [29]. On the other hand, aging and obesity have also been associated with alterations in G-protein subunit expression [27,30]. These modifications at the level of signal transduction may well reflect mechanisms by which the lipolytic response of adipose tissue, among others, is regulated in different physiological circumstances.…”
Section: Resultsmentioning
confidence: 99%
“…A similar result was obtained for genetically obese (ob/ob) mice compared with lean littermates (Begin-Heick 1990). Preferential change of the short isoform was found in white adipocytes of aged rats, which exhibited a marked increase in G s S detected by both immunoblotting and cholera toxin-induced ADP ribosylation (Green & Johnson 1989). Interestingly, an identical reduction in both G s subforms was also reported in the adipocytes of obese (fa/fa) Zucker rats (Strassheim et al 1991).…”
Section: The (Non)identity Of the Short And Long Variants Of G Ssupporting
confidence: 66%
“…A diminished response of the receptoraG proteinaadenylyl cyclase membrane complex or alterations in the cyclic AMP signaling pathway have been shown to occur with age in rats (Gregerman, 1994). Other studies have shown increased sensitivity to antilipolytic agents, such as adenosine, in older rats (Green & Johnson, 1989;Hoffman et al, 1984). A recent study comparing young lean versus old obese Sprague Dawley rats was performed to examine age effects on stimulatory (G S ) and inhibitory (G i GTP-binding proteins.…”
Section: Effects Of Age On the Recruitment Of Fat Substrates: In Vitrmentioning
confidence: 99%